Can an Energy Futures Index Predict US Stock Market Index Movements? - Gurrib, Ikhlaas (International Journal of Energy Economics and Policy, 2018)
This paper investigates if an energy futures conditions index (EFCI) can predict movements of US major stock market indices. While various financial conditions indices provide information about the financial stress of a country, the existence of an energy conditions index, using futures markets, is scarce. Using weekly data over 1992-2017, this paper proposes an energy futures index using principal component analysis and test its predictability. The EFCI captures 95% of the variability inherent in the crude oil, heating oil and natural gas futures total reportable positions. Stability in forecast errors over different lags suggests one week lag is sufficient in forecasting weekly Nasdaq Composite Index, Nasdaq 100 and Russell 3000 values. 95% prediction levels support that the estimated model captures all actual market indices values, except for the 2000 technology bubble. The inability of the energy futures index in predicting stock market indices during the 2000 bubble can be explained by the poor sensitivity of energy futures to this specific event. Distributions were non-normal, not serially correlated and homoscedastic under the whole sample period, with diagnostics on pre and post technology bubble crisis showing mixed results. Keywords: energy futures, stock market index, reportable positions JEL Classifications: G15, G18, Q47